The Golden Horn: Potentials on Touristic and Cultural Identity - Buket Onem (European Regional Science Association (ERSA), 2006)
Cities are places where human needs such as: settlement, residential accommodation, work places, recreation and entertainment are satisfied, services are provided. Social and cultural aspects of the city are the most important features which are in a continuous development. Urban identity in this respect is very vital for cities in order to survive as a living organism and provide livable environment for the urbanites. As a world metropolis Istanbul is a unique city with her natural environment, historical and archeological heritage and very vivid socio-cultural life. These features provide a rich identity and at the same time allow for a powerful urban image. Her silhouette created by physical elements and historical architecture is very impressive. Golden Horn being a gulf along the Bosphorus is an important element of the urban physical structure and has a special role in the historical and cultural life of Istanbul. Within the comprehensive image of the metropolitan Istanbul, it is a sub-region with strong elements of identity. These elements can be identified by the data related to the natural, cultural and human environment. Golden Horn sub-region should be evaluated after a meticulous assessment of the touristic potential, quality of urban services provided and a comprehensive investigation on the sub-regional identity. During the last two decades local governments have frequently displayed a fragmented approach in the preparation of area developmental plans without any research on identity. One of the main objectives of this study is to provide a comprehensive investigation on the identity elements in order to constitute a base for future improvement and physical planning studies. Another important aim of the study is the definition or delimitation of an historical sub-region of Istanbul. The end products of this study will help to determine the policies and plans to enhance the economic base of the area, to define the physical, cultural and social elements of the identity of the Golden Horn region.
Keywords: 330